2011
DOI: 10.1108/09699981111180926
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing technical innovation in construction SMEs: an Australian perspective

Abstract: PurposeThe intent of this research is to determine whether any common lessons can be drawn from the experience of individuals who have gone against the trend and delivered successful technical innovations in construction small and medium enterprises (SMEs).Design/methodology/approachA value tree of contributing factors to technical innovation was developed from the literature and tested by surveying established technical innovators using analytic hierarchy process methodology. This approach aimed at capturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 61 publications
2
74
0
1
Order By: Relevance
“…However, many scholars reported that the characteristics of the construction industry worldwide, as well as Malaysia, are dominated by small-medium firms and, thus, it should be well sustained. Furthermore, Hardie (2010) along Hardie and Newell (2011) believe that if sufficient support and encouragement are provided to the small-medium construction businesses, they would be able to deliver a potentially significant contribution to the economic and environmental performance of the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, many scholars reported that the characteristics of the construction industry worldwide, as well as Malaysia, are dominated by small-medium firms and, thus, it should be well sustained. Furthermore, Hardie (2010) along Hardie and Newell (2011) believe that if sufficient support and encouragement are provided to the small-medium construction businesses, they would be able to deliver a potentially significant contribution to the economic and environmental performance of the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…A potential reason why customer embeddedness does not relate to novel products is that customers are often risk-averse toward novel innovation. In construction industries in particular, customers are strongly reputed for seeking low-risk solutions (Barrett & Sexton, 2006;Daneshy & Donnelly, 2004;Hardie & Newell, 2011) and often view novel innovation as a risk factor to be avoided (Keegan & Turner, 2002). If these assertions hold true in this research setting, it is not surprising then that customers are not (either positively or negatively) related to novel product innovations because they simply do not influence these outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…On the negative side of the argument, in CoPS industries like construction and oil and gas, customers have distinct reputations for being incrementally innovative (Barrett & Sexton, 2006;Daneshy & Donnelly, 2004;Hardie & Newell, 2011;Keegan & Turner, 2002;Manley, 2008;Reichstein & Salter, 2006). In these environments, customers may view innovation as costly, risky and even dangerous (Keegan & Turner, 2002).…”
Section: Customer Embeddednessmentioning
confidence: 99%
See 2 more Smart Citations